1977
DOI: 10.1017/s0022172400053183
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pregnancies at risk from cytomegalovirus infection

Abstract: SUMMARYThe fluorescent antibody technique was used for the identification of specific cytomegalovirus IgM in the sera of twenty-four of 1065 unmarried pregnant women. Seventeen of them were followed to term and five infected infants were identified. Two other infants had CMV IgM in neonatal serum samples but virus excretion was not demonstrated. The congenital infection rate in this study was 5-3 per 1000 births by virus excretion and 7'9 per 1000 if cases with specific IgM are included; from previous studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1979
1979
1993
1993

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 12 publications
(7 reference statements)
0
11
0
Order By: Relevance
“…Recurrent as well as primary infection during pregnancy can affect the fetus [Stagno et al, 1977, 19821, but primary infection is the principal cause of fetal damage [Fowler et al, 19921. In Western countries, including the UK, 0.3-0.5% of babies are born infected with CMV [De Silva et al, 1977;Stern and Tucker, 1973;Ahlfors et al, 19841. Most of these cases are the consequence of primary infection in the mother, which crosses the placenta in 20-50% of cases [Griffiths and Baboonian, 1984;Kumar et al, 19841.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent as well as primary infection during pregnancy can affect the fetus [Stagno et al, 1977, 19821, but primary infection is the principal cause of fetal damage [Fowler et al, 19921. In Western countries, including the UK, 0.3-0.5% of babies are born infected with CMV [De Silva et al, 1977;Stern and Tucker, 1973;Ahlfors et al, 19841. Most of these cases are the consequence of primary infection in the mother, which crosses the placenta in 20-50% of cases [Griffiths and Baboonian, 1984;Kumar et al, 19841.…”
Section: Introductionmentioning
confidence: 99%
“…The blood donor CMV status was determined by immunofluorescence (IF) (de Silva et al, 1977) for 52 of the 64 babies. 21 babies received blood from at least one CMV antibody-positive donor and 8 (38%) became infected, while the 31 babies who received only CMV antibody-free blood remained uninfected.…”
Section: Resultsmentioning
confidence: 99%
“…For CMV antibody determination we used the IF antibody test (de Silva et al, 1977) as it is more sensitive than the complement-fixation (CF) test and quicker to perform, a result being obtained in 2 hours as opposed to the overnight incubation required for the CF test. Our results using this IF test in exchange transfused babies indicates that it is satisfactory for blood screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that detection of CMV IgM in the mother is another risk factor for fetal infection, but its precise meaning was not clarified. DeSilva et al (1977) followed 1065 unmarried pregnant women in Manchester, England and identified 24 with specific lgM antibodies by IF in their sera; of these, 17 were followed to term. As in the report of , separate objective definitions of primary and secondary CMV infection were inadequate, and the sensitivy and specificity of the test could not be determined.…”
Section: Immunagiobulin M Studies In Pregnant Mothersmentioning
confidence: 99%